PENGARUH PRODUKTIVITAS LAHAN, TEKNOLOGI PERTANIAN, DAN KEBIJAKAN PEMERINTAH TERHADAP PENGEMBANGAN EKONOMI LOKAL SEKTOR PADI - Agu Sujana; Zam Zami; Zainul Bahri; Siti Hodijah; Nurhayani (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
Local economic development in rural areas is significantly influenced by the performance of the agricultural sector, particularly the rice subsector. Various studies have shown that land productivity, the application of agricultural technology, and government policy support are key factors in driving agriculture-based local economic growth. This article aims to analyze the influence of these three factors on local economic development through a literature review and policy analysis approach. The methods used were a literature review of national and international journal articles published between 2018 and 2025 and a review of national and regional agricultural policy documents. The study results indicate that increasing land productivity directly contributes to increased farmer income and local economic activity. The application of agricultural technology has been shown to increase production efficiency and yield stability, while government policy acts as a facilitator in accelerating technology adoption and maintaining the sustainability of farming businesses. However, the weak integration between productivity, technology, and policy has resulted in the rice sector's contribution to the local economy being suboptimal. This article emphasizes the importance of synergy between agricultural policies and innovation as a foundation for sustainable local economic development.